Chemical composition and antimicrobial of essential oil from Artemisia Lehmanniana - Alireza Sardashti,; A. Ganjali, (International Journal of Phytomedicine, 2013)
The plants of A.Lehmanniana were gathered in May 2009 from the heights of 2300 m of Taftan Mountain located in Baluchestan. Its essential oil was extracted with an outcome of 1.34%w/w, using hydro distillation method. Then, using GC/MS technique, it was analyzed and 54components were recognized that constituted 96.61%of the whole essential oil. The components that had the highest percentage were as Follow: 1, 8- Cineole (22.06%), (z)-2-Nonenal (12.11%), Nonaconsane (8.97%), α-Terpineol (5.90%), 4-Terpineol (5.07%), Camphor (4.19%) and unknown compound (4. 41%). Antimicrobial effects of this essential oil were exactly estimated and examined in Laboratory. Its sensitiveness (Minimal inhibition Concentration) to mentioned-micro-organisms in the following: Staphylococcus aureus (4μg/ml), Salmonella typhi (32μg/ml), Escherichia coli (32μg/ml), Candida albicans (8μg/ml), Aspergillus Niger (4 μg/ml), showed that the highest was recognized by comparing with standard samples with the way of dilution and minimum controlling concentration was calculated. As the results revealed, the micro-organism of Pseudomonas aeruginosa could be controlled in higher concentrations.